Dualization as Destiny? The Political Economy of the German Minimum Wage Reform. (December 2017) - Marx, Paul; Starke, Peter
Germany is widely seen as a "dualized" economy driven by a powerful and stable "insider" coalition in the manufacturing sectors. In this article, that picture is challenged. An examination of the political economy of the outsider-friendly 2014 Minimum Wage Act, using public opinion data, document analysis, and qualitative interviews, shows how earlier dualizing reforms led to unintended negative feedback effects: First, public opinion reacted negatively to increasing inequality in the years preceding the introduction of the minimum wage. Second, a remarkable shift is found among trade unions toward support of a minimum wage, even in manufacturing. Although the threat of low-wage competition and flexibilization did play a role, trade union solidarity was at least as important. Those endogenous dynamics came together in a self-undermining process unfolding over a relatively short period of time. Potential alternative explanations are explored, including classical partisan politics, party competition, and employer preferences.